How did Maharashtra cut child stunting? - Haddad, Lawrence (International Food Policy Research Institute, 2014)
Implementation fidelity is defined by adherence to intervention design, exposure or dose, quality of delivery, and participant responsiveness. As part of the process evaluation (PE) of Alive & Thrive, a large‐scale initiative to improve IYCF, our study assessed the four elements in training of frontline workers (FLWs), delivery of program tools and messages, and supervision and feedback. Data from a qualitative study among three levels of FLWs (n=54 in 2012), i.e. supervisors, health extension workers (HEWs), and community volunteers; and baseline and PE surveys with FLWs (n=225 in 2010, n=504 in 2013) and mothers (n=1,481 in 2010, n=750 in 2013) in two regions (Tigray and SNNPR) were analyzed to examine fidelity of key program components. There was strong adherence to intended cascading format (i.e. information transfer from higher to lower FLW levels) and high exposure to training (95% HEWs and 94% volunteers in Tigray, 68% and 81% respectively in SNNPR). Training quality, assessed by IYCF knowledge and self‐reported capacity, was high and increased since baseline. Job aids were used regularly by most supervisors and HEWs, but only 54% of volunteers in Tigray and 39% in SNNPR received them. Quality of program message delivery was lower among volunteers, and aided recall of key messages among mothers was also low. Although supervision exposure was high, frequency was irregular with weak content fidelity. There is evidence of strong fidelity in training and delivery of tools and messages at higher FLW levels, but gaps in the reach of these to volunteers and mothers and variability between regions limit the potential for intervention impact.Grant Funding Source: Supported by: Bill & Melinda Gates Foundation, through Alive & Thrive, managed by FHI360